Drivers of methane-cycling archaeal abundances, community structure, and catabolic pathways in continental margin sediments - Longhui Deng; Longhui Deng; Damian Bölsterli; Clemens Glombitza; Bo Barker Jørgensen; Hans Røy; Mark Alexander Lever; Mark Alexander Lever (Frontiers in Microbiology)
Marine sediments contain Earth’s largest reservoir of methane, with most of this methane being produced and consumed in situ by methane-cycling archaea. While numerous studies have investigated communities of methane-cycling archaea in hydrocarbon seeps and sulfate–methane transition zones, less is known about how these archaea change from the seafloor downward throughout diffusion-dominated marine sediments. Focusing on four continental margin sites of the North Sea-Baltic Sea transition, we here investigate the in situ drivers of methane-cycling archaeal community structure and metabolism based on geochemical and stable carbon-isotopic gradients, functional gene (mcrA) copy numbers and phylogenetic compositions, and thermodynamic calculations. We observe major changes in community structure that largely follow vertical gradients in sulfate concentrations and lateral gradients in organic carbon reactivity and content. While methane-cycling archaeal communities in bioturbated and sulfatic zones are dominated by known methyl-disproportionating Methanosarcinaceae and putatively CO2-reducing Methanomicrobiaceae, the communities change toward dominance of methane-oxidizing taxa (ANME-2a-b, ANME-2c, ANME-1a-b) in sulfate–methane transition zones (SMTZs). By contrast, the underlying methanogenesis zones are dominated by the physiologically uncharacterized ANME-1d, new genus-level groups of putatively CO2-reducing Methanomicrobiaceae, and methyl-reducing Methanomassiliicoccales. Notably, mcrA copy numbers of several major taxa increase by 2 to 4 orders of magnitude from the sulfatic zone into the SMTZ or methanic zone, providing evidence of net population growth in subsurface sediment. We propose that burial-related geochemical changes cause methane-cycling archaea in continental margin sediments to go through three successional stages (sulfatic, SMTZ, methanic). Herein, the onset of each new successional stage is characterized by a period of growth- and mortality-driven turnover in the dominant taxa.